The variability of physical match demands in elite women`s football - Baptista, I.; Winther, A. K.; Johansen, D.; Randers, M. B.; Pedersen, S.; Pettersen, S. A. (Science and Medicine in Football, 2022)
Peak locomotor demands are considered as key metrics for conditioning drills prescription and training monitoring. However, research in female football has focused on absolute values when reporting match demands, leading to sparse information being provided regarding the degrees of variability of such metrics. Thus, the aims of this study were to investigate the sources of variability of match physical performance parameters in female football players and to provide a framework for the interpretation of meaningful changes between matches.